2013
DOI: 10.1103/physreve.87.042306
|View full text |Cite
|
Sign up to set email alerts
|

Measuring spatial distribution of the local elastic modulus in glasses

Abstract: Glasses exhibit spatially inhomogeneous elastic properties, which can be investigated by measuring their elastic moduli at a local scale. Various methods to evaluate the local elastic modulus have been proposed in the literature. A first possibility is to measure the local stress-local strain curve and to obtain the local elastic modulus from the slope of the curve, or equivalently to use a local fluctuation formula. Another possible route is to assume an affine strain and to use the applied global strain inst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
169
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(177 citation statements)
references
References 40 publications
6
169
2
Order By: Relevance
“…The shear and bulk modulus, G 2 = 17 and K 2 = 98, have been measured with the method described in Ref. 23; the associated Poisson ratio is ν 2 = 0.70 (the subscript is used to indicate two-dimensional quantities).…”
Section: A Modelmentioning
confidence: 99%
“…The shear and bulk modulus, G 2 = 17 and K 2 = 98, have been measured with the method described in Ref. 23; the associated Poisson ratio is ν 2 = 0.70 (the subscript is used to indicate two-dimensional quantities).…”
Section: A Modelmentioning
confidence: 99%
“…In particular, a correlation length of tens of interatomic distances has been revealed in the nonaffine displacement field of various simulated glasses * giacomo.baldi@cnr.it under an external perturbation [4,5]. Numerical simulations of polymeric glasses [6,7] and of Lennard-Jones and softsphere systems [8,9] indicate that the local elastic modulus is heterogeneous and the width of its distribution increases as the length scale over which it is computed is reduced, implying that on the macroscopic scale these fluctuations are averaged out. However, at present, the numerical works do not indicate a length scale for the heterogeneities, although there have been indications for a fractal-like distribution of the local elastic modulus [7].…”
Section: Introductionmentioning
confidence: 96%
“…Recent numerical simulation studies have revealed that the elasticity of glasses is heterogeneous on the nanometer length scale [4][5][6][7][8][9], suggesting a possible relation with the dynamical heterogeneities above T g . In particular, a correlation length of tens of interatomic distances has been revealed in the nonaffine displacement field of various simulated glasses * giacomo.baldi@cnr.it under an external perturbation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a better atomic volume model for the free surface layer will lead to improved 21 results. Overall, this new approach will be a powerful tool for the modeling and simulation of other inhomogeneous materials, such as the interphase of polymer-based nano-composites [45], interface formed between different crystallographic directions [46], etc.…”
Section: Discussionmentioning
confidence: 99%
“…For the deformation-based technique [20], Mizuno et al compared with three different approaches by using the same glassy materials [7,21]. In order to suppress the fluctuation of stresses and strains, the simulation temperature is extremely low.…”
Section: Introductionmentioning
confidence: 99%